Factors Associated with the Occurrence of Stunting in Naibonat Village, Kupang Regency, East Nusa Tenggara, in 2022 - Wehelmince Sisilia Cantika Dasi Muda; Marselinus Laga Nur; Rut Rosina Riwu (Journal of Health Promotion and Behavior, 2023)
Background: Stunting is a condition of failure to thrive in children under five years old (children under five) due to chronic malnutrition in the First 1000 Days of Life (HPK) and is based on the BB/U or TB/U index with a z-score limit of less than -2 SD to - 3 SD. Stunting can be caused by several factors, namely exclusive breastfeeding, father's education, mother's education, family income, number of children. The purpose of this study is to determine the factors associated with the incidence of stunting in the Naibonat Village, Kupang Regency in 2022. Subjects and Method: This is a case-control study conducted in Naibonat Village, East Kupang, Kupang, East Nusa Tenggara, in September-October 2022. There were 134 children under five consisting of 67 stunted children under five and 67 children under five who were not stunted. The dependent variable is the incidence of stunting. The independent variables were exclusive breastfeeding, history of infectious diseases, father's education, mother's education, family income, history of LBW, and number of children. Data were collected using observation sheets and analyzed using the chi-square test. Results: Not exclusively breastfed (OR= 4.12; 95% CI= 1.84 to 9.24; p< 0.001), history of father's education was low (OR= 0.34; 95% CI= 0.13 to 0.89; p= 0.024), history of mother's education was low (OR= 0.17; 95% CI= 0.04 to 0.65; p= 0.004), low family income (OR= 0.23; 95% CI= 0.08 to 0.62; p= 0.002), and history of LBW (OR= 0.48; 95% CI= 0.40 to 0.51; p= 0.042) related to the incidence of stunting, and statistically significant. Conclusion: A history of exclusive breastfeeding, a history of low father education, a history of low maternal education, low family income, and a history of LBW are statistically related to the incidence of stunting. Keywords: stunting, risk factors, children under five. Correspondence: Wehelmince Sisilia Cantika Dasi Muda. Study Program of Public Health, Faculty of Public Health, Universitas Nusa Cendana. Jl. Adisucipto Penfui, Kupang, East Nusa Tenggara Timur. Email: sisiliadasimuda09@gmail.com. Mobile: +62 813-3901-4476.